Childhood maltreatment and DNA methylation: A systematic review. (April 2023) - Rubens, Mackenzie; Bruenig, Dagmar; Adams, Jessica A.M.; Suresh, Shruthi M.; Sathyanarayanan, Anita; Haslam, Divna; Shenk, Chad E.; Mathews, Ben; Mehta, Divya
Abstract: Child maltreatment (CM) encompasses sexual abuse, physical abuse, emotional abuse, neglect, and exposure to domestic and family violence. Epigenetic research investigating CM has focused on differential DNA methylation (DNAm) in genes associated with the stress response, but there has been limited evaluation of the specific effects of subtypes of CM. This systematic review of literature investigating DNAm associated with CM in non-clinical populations aimed to summarise the approaches currently used in research, how the type of maltreatment and age of exposure were encoded via methylation, and which genes have consistently been associated with CM. A total of fifty-four papers were eligible for review, including forty-one candidate gene studies, eight epigenome-wide association studies, and five studies with a mixed design. The ways in which the various forms of CM were conceptualised and measured varied between papers. Future studies would benefit from assessments that employ conceptually robust definitions of CM, and that capture important contextual information such as age of exposure and subtype of CM. Highlights: We review original research on childhood maltreatment and DNA methylation. The 54 studies were mainly cross-sectional and candidate-gene focussed. Methodological errors and weak conceptualisations of maltreatment were common. Measurement tools of included studies did not capture all necessary information. Few studies investigate the associated effects of maltreatment subtypes.